Provider Perspectives on the Extension for Community Healthcare Outcomes Autism: Transition to Adulthood Program. Issue 2 (February 2021) - Cheak-Zamora, Nancy; Farmer, Justin G.; Crossman, Morgan K.; Malow, Beth A.; Mazurek, Micah O.; Kuhlthau, Karen; Stobbe, Gary; Loftin, Rachel; Mirza-Agrawal, Mavara; Tapia, Mark; Hess, Amy; Davis, Katrina; et al.
ABSTRACT: Objective: Despite their complex health care needs, transition-aged youth diagnosed with autism spectrum disorder (TAY-ASD) receive few transition services and describe difficulty finding adult providers. A 12-week primary care provider (PCP) training was developed to improve the delivery of transition services for TAY-ASD [Extension for Community Healthcare Outcomes (ECHO) Autism: Transition to Adulthood program]. The current study examines the PCPs' perspectives and experiences of the program and application of the training material. Methods: This study used a qualitative descriptive framework to explore the experiences and perspectives of 10 PCPs who completed the ECHO Autism: Transition to Adulthood program. Semistructured focus groups, conducted through Zoom videoconferencing, were used to explore these topics. Results: Three overarching categories were identified: (1) beneficial and influential aspects of the ECHO, (2) perceived challenges, and (3) suggestions for improvements and adjustments. Overall, participants found the program highly beneficial, describing an increased sense of community and comprehensive recommendations from a multidisciplinary team. Challenges included difficulties participating in the program during clinical hours and difficulties meeting the educational needs of participants with a wide range of previous experience caring for TAY-ASD. Recommendations included embedding the location-specific material into the program to account for regional differences and the use of an online platform for participants to ask questions and discuss issues outside of the regular sessions. Conclusion: The study results can inform the development and implementation of new virtual PCP trainings and future ECHOs, including the revision and broad implementation of the ongoing ECHO Autism: Transition to Adulthood program.